Genetic Diversity of Composite Enterotoxigenic Staphylococcus epidermidis Pathogenicity Islands. (26th November 2019) - Banaszkiewicz, Sylwia; Calland, Jessica K; Mourkas, Evangelos; Sheppard, Samuel K; Pascoe, Ben; Bania, Jacek
Abstract: The only known elements encoding enterotoxins in coagulase-negative staphylococci are composite Staphylococcus epidermidis pathogenicity islands (SePIs), including SePI and S. epidermidis composite insertion (SeCI) regions. We investigated 1545 Staphylococcus spp. genomes using whole-genome MLST, and queried them for genes of staphylococcal enterotoxin family and for 29 ORFs identified in prototype SePI from S. epidermidis FRI909. Enterotoxin-encoding genes were identified in 97% of Staphylococcus aureus genomes, in one Staphylococcus argenteus genome and in nine S. epidermidis genomes. All enterotoxigenic S. epidermidis strains carried composite SePI, encoding sec and sel enterotoxin genes, and were assigned to a discrete wgMLST cluster also containing genomes with incomplete islands located in the same region as complete SePI in enterotoxigenic strains. Staphylococcus epidermidis strains without SeCI and SePI genes, and strains with complete SeCI and no SePI genes were identified but no strains were found to carry only SePI and not SeCI genes. The systematic differences between SePI and SeCI regions imply a lineage-specific pattern of inheritance and support independent acquisition of the two elements in S. epidermidis. We provided evidence of reticulate evolution of mobile elements that contain elements with different putative ancestry, including composite SePI that contains genes found in other coagulase-negative staphylococci (SeCI), as well as in S. aureus (SePI-like elements). We conclude that SePI-associated elements present in nonenterotoxigenic S. epidermidis represent a scaffold associated with acquisition of virulence-associated genes. Gene exchange between S. aureus and S. epidermidis may promote emergence of new pathogenic S. epidermidis clones.